Government Securities Versus Central Bank Securities in Developing Open Market Operations Evaluation and Need for Coordinating Arrangements - Quintyn, Marc (International Monetary Fund, 1994)
In an indirect monetary policy framework, open market operations become the central bank's main instrument. In the initial stages, when financial markets are still undeveloped, selection of a financial instrument for those operations and the design of supporting arrangements to ensure the central bank's operational autonomy when using the instrument, are crucial issues. Based on theoretical arguments and experience of a sample of countries that embarked on financial reforms, this paper argues that government securities are the preferred instrument because of their better capacity to develop financial markets. The use of government securities, however, requires the most complex supporting arrangements